1970
DOI: 10.1029/jc075i024p04583
|View full text |Cite
|
Sign up to set email alerts
|

Dust devil properties

Abstract: Measurements of electric moment are reported for seventeen New Mexico dust devils. Estimates of charge and charge density were made for eight of these; charge densities appear generally to be of the order of 106 elementary charges cm−3. Ground speeds ranged from 5–11 m sec−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…It was found that the electric field was upward pointing in dust devils. Freier's findings were later confirmed by Crozier (1964Crozier ( , 1970. These pioneering measurements of dust devil electric fields are consistent with results of more recent measurements Fig.…”
Section: Surface Measurementssupporting
confidence: 78%
“…It was found that the electric field was upward pointing in dust devils. Freier's findings were later confirmed by Crozier (1964Crozier ( , 1970. These pioneering measurements of dust devil electric fields are consistent with results of more recent measurements Fig.…”
Section: Surface Measurementssupporting
confidence: 78%
“…The time evolution of space charge density is very similar to the initial accumulation of the thunderstorm space charge in the QE heating model before a conventional breakdown is reached [Pasko et al, 1997]. This maximum electric field for a typical terrestrial dust devil is difficult to compare with experimental measurements, all of which have strongly saturated at a few kV/m [Freier, 1960;Crozier, 1964Crozier, , 1970Farrell et al, 2004], but the predicted value of 150 kV/m is not inconsistent with these measurements. Very recently, Jackson and Farrell (submitted man- Melnik and Parrot [1998], the dissipation of dust grain charge due to atmospheric conductivity is fully considered in our FE simulation.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 73%
“…The modeled terrestrial dust devil electric field reaches breakdown value (3 MV/m) in less than 5 min. This model predicts unlimited growth of dust devil electric fields that are not consistent with past observations of terrestrial dust devils, where only a maximum electric field of a few kV/m has been observed [Crozier, 1970;Farrell et al, 2004]. Most recently, Jackson and Farrell (submitted manuscript, 2005) measured near 120 kV/m QE fields of dust devils with a carefully calibrated electrometer.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations